Konstruksi Wacana Feminisme di Media Sosial (Analisis Framing Instagram @mubadalah.id) - Serin Himatus Soraya; Sri Mulyani (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2026)
This study aims to analyze how feminist narratives are constructed through the Instagram content of @mubadalah.id during September 2025. The account was selected because of its consistent engagement with gender equality issues grounded in Islamic values. The research employs a qualitative approach with Pan & Kosicki’s framing analysis model, encompassing syntactic, script, thematic, and rhetorical structures. The unit of analysis consists of Instagram feed posts in September 2025, focusing on 4 posts explicitly addressing gender equality. The findings reveal that feminist framing in @mubadalah.id is consistently highlighting gender inequality, shifting the focus from biased narratives toward the recognition of women as active subjects, and combining rhetorical strategies that employ emotion (pathos), data and religious legitimacy (logos), as well as moral authority (ethos). This study contributes to media, communication, and gender studies by demonstrating how Instagram serves as a significant digital da’wah arena that integrates religious interpretation with gender equality narratives in a popular communication format.